Implementing best practices on data generation and reporting of Mycobacterium tuberculosis in vitro assays within the ERA4TB consortium - Rob C. van Wijk; Ainhoa Lucía; Pavan Kumar Sudhakar; Lindsay Sonnenkalb; Cyril Gaudin; Eik Hoffmann; Bérénice Dremierre; Diana Angélica Aguilar-Ayala; Michael Dal Molin; Jan Rybniker; Stefano de Giorgi; Laura Cioetto-Mazzabò; et al. (iScience, 2023)
Summary: Tuberculosis (TB) is the historical leading cause of death by a single infectious agent. The European Regimen Accelerator for Tuberculosis (ERA4TB) is a public-private partnership of 30+ institutions with the objective to progress new anti-TB regimens into the clinic. Thus, robust and replicable results across independent laboratories are essential for reliable interpretation of treatment efficacy. A standardization workgroup unified in vitro protocols and data reporting templates. Time-kill assays provide essential input data for pharmacometric model-informed translation of single agents and regimens activity from in vitro to in vivo and the clinic. Five conditions were assessed by time-kill assays in six independent laboratories using four bacterial plating methods. Baseline bacterial burden varied between laboratories but variability was limited in net drug effect, confirming 2.5 μL equally robust as 100 μL plating. This exercise establishes the foundations of collaborative data generation, reporting, and integration within the overarching Antimicrobial Resistance Accelerator program.